A comparative evaluation of the effect of liners on the shear bond strength of veneered zirconia block: An in vitro study - Pooja Yadav; Nupur Dabas; Sumit Singh Phukela; Puja Malhotra; Shefali Drall; Pankaj Kumar Ritwal (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aims to evaluate the effect of lithium disilicate glass-ceramic liner, silicon dioxide based liner, and glass-ceramic interlayer on the shear bond strength (SBS) of a commercially available veneered zirconia block and to study fractographic behavior of the samples using universal testing machine, scanning electron microscope (SEM). Setting and Design: In vivo - comparative study. Materials and Methods: 60 samples were fabricated from VITA (vita zahnfabrik. Bad sackingen, Germany) zirconia discs. Samples were divided into 4 groups with 15 samples each. First is the control group, second is lithium disilicate glass-ceramic liner group, third is silicon dioxide based liner, and fourth is glass-ceramic interlayer group. SBS of samples was recorded using universal testing machine. Samples were further analyzed for fractographic behavior using SEM. Statistical Analysis Used: One Way ANOVA test, and Chi-Square test. Results: The intergroup comparison of mean SBS (Mpa) was done using the post hoc Bonferroni test. The mean SBS (Mpa) was significantly more among lithium disilicate and glass-ceramic interlayer groups in comparison to silicon dioxide-based liner group. Fractographic analysis was done using the Chi-square test. Conclusion: It was concluded that maximum SBS was obtained for lithium disilicate liner. Maximum adhesive failures were found with lithium disilicate liner, and silicon dioxide-based liner group showed cohesive failures.